Effect of variants in LGP2 on MDA5-mediated activation of interferon response and suppression of hepatitis D virus replication - Gillich, Nadine; Zhang, Zhenfeng; Binder, Marco; Urban, Stephan; Bartenschlager, Ralf (Journal of hepatology, 2023)
Background & Aims - Retinoic acid inducible gene I (RIG-I)-like receptors (RLRs), including RIG-I, melanoma differentiation-associated protein 5 (MDA5), and laboratory of genetics and physiology 2 (LGP2), sense viral RNA to induce the antiviral interferon (IFN) response. LGP2, unable to activate the IFN response itself, modulates RIG-I and MDA5 signalling. HDV, a small RNA virus causing the most severe form of viral hepatitis, is sensed by MDA5. The mechanism underlying IFN induction and its effect on HDV replication is unclear. Here, we aimed to unveil the role of LGP2 and clinically relevant variants thereof in these processes. - Methods - RLRs were depleted in HDV susceptible HepaRGNTCP cells and primary human hepatocytes. Cells were reconstituted to express different LGP2 versions. HDV and IFN markers were quantified in a time-resolved manner. Interaction studies among LGP2, MDA5, and RNA were performed by pull-down assays. - Results - LGP2 is essential for the MDA5-mediated IFN response induced upon HDV infection. This induction requires both RNA binding and ATPase activities of LGP2. The IFN response only moderately reduced HDV replication in resting cells but profoundly suppressed cell division-mediated HDV spread. An LGP2 variant (Q425R), predominating in Africans who develop less severe chronic hepatitis D, mediated detectably higher basal and faster HDV-induced IFN response as well as stronger HDV suppression. Mechanistically, LGP2 RNA binding was a prerequisite for the formation of stable MDA5-RNA complexes. MDA5 binding to RNA was enhanced by the Q425R LGP2 variant. - Conclusions - LGP2 is essential to mount an antiviral IFN response induced by HDV and stabilises MDA5-RNA interaction required for downstream signalling. The natural Q425R LGP2 is a gain-of-function variant and might contribute to an attenuated course of hepatitis D. - Impact and implications - HDV is the causative pathogen of chronic hepatitis D, a severe form of viral hepatitis that can lead to cirrhosis and hepatocellular carcinoma. Upon infection, the human immune system senses HDV and mounts an antiviral interferon (IFN) response. Here, we demonstrate that the immune sensor LGP2 cooperates with MDA5 to mount an IFN response that represses HDV replication. We mapped LGP2 determinants required for IFN system activation and characterised several natural genetic variants of LGP2. One of them reported to predominate in sub-Saharan Africans can accelerate HDV-induced IFN responses, arguing that genetic determinants, possibly including LGP2, might contribute to slower disease progression in this population. Our results will hopefully prompt further studies on genetic variations in LGP2 and other components of the innate immune sensing system, including assessments of their possible impact on the course of viral infection.
Online verfügbar 22 September 2022, Version des Artikels 15 December 2022
Gesehen am 29.03.2023